Relational values of forests: Value-conflicts between local communities and external programmes in Sulawesi - Yuliani, E.L.; Moeliono, M.; Labarani, A.; Fisher, M.R.; Tias, P.A.; Sunderland, T.C.H. (Wiley, 2023)
Studies found that rapid decline of biodiversity and ecosystems globally have adversely affected an estimated 1.6 billion rural people whose livelihoods both directly and indirectly depend on forests. To halt the loss of forests and other natural ecosystems that simultaneously support rural livelihoods, various external programmes have been developed and applied, including market-based and rights-based approaches. However, rapid biodiversity and ecosystem decline continues, and better incentives or more secure rights have not always led to local community participation and improved livelihoods. This suggests the need to better explain local communities' motivations in nature stewardship. We conducted a study of local communities in two villages in Sulawesi who voluntarily maintain forests but showed resistance to participation in formal Social Forestry programmes. The study aimed to identify motivations and underlying reasons of community preferences, guided by two research questions: (i) how did local people value forest landscapes? and (ii) how did those values interact with externally driven Social Forestry programmes? We applied the Relational Values concept to understand a community's relations with the forest (or its elements) and land and identified points of value divergence. Data collection involved in-depth semi-structured interviews, focus group discussions framed by the principles of Appreciative Inquiry, participant observation and land use/land cover change analysis. Our findings show that people value their forests in relation to their identity, ancestral heritage, sense of place and spiritual values. We also identified the points of value divergence and their underlying reasons of resistance towards externally driven forestry programmes. This study thus contributes to the broader conceptualisation of values in conservation and community participation by providing empirical evidence on the importance of the Relational Values framework in understanding the motivation and behaviour of nature stewardship and in the evaluation of value conflicts.